The role of the transfusion safety coordinator in Australia. (29th January 2016) - Bielby, L.; Akers, C.; Francis, S.; Darby, S.; Campbell, L.; Hollis, L.; Quested, B.; Hogan, C.
Abstract : Transfusion safety coordinators (TSCs) are an integral part of the transfusion process, which involves many interlinking chains of events and a multidisciplinary group of health professionals. In Australia, individual hospital‐based TSCs have been in place for several decades, with state‐based collaboratives commencing in 2002. The role has expanded across the country and currently there are 113 dedicated TSC positions and many more staff involved as blood/transfusion champions. There are also 12 transfusion nurse (TN) positions within the Australian Red Cross Blood Service. Over time both TSC and TN roles have evolved to meet the changes within the Australian blood sector. The primary focus of safety and appropriateness has now evolved to be more patient‐centred by incorporating patient blood management (PBM) initiatives. National PBM guidelines, statements, strategies, criteria and healthcare standards specifically focused on all aspects of transfusion have influenced this evolution. TSCs undertake diverse roles and activities that vary significantly between health services and within each jurisdiction. Effective communication and change management skills are integral to the success of the role. Conclusion: The TSCs are highly recognised within the transfusion team and the role continues to evolve with the changes in the Australian blood sector. The term Transfusion Safety Coordinators (TSCs) has been used to describe roles such as transfusion nurse/trainer/practitioner/safety officer/clinical nurse consultant and PBM nurses.